Identifikasi Karakter Morfologi Dan Agronomi Tanaman Padi F1 Hasil Silang Balik Resiprok Kambang/Pandan Ungu//Pandan Ungu - hadi pranoto; Akhmad Askan; Bambang Supriyanto (Mulawarman University, 2019)
This research was conducted to obtain hybridization which has superior character and to know the agronomic and morphological characters of F1 generation from reciprocal crossof Kambang/Pandan Ungu//Pandan Ungu, this research uses a reciprocal cross method (cross between F1 from a single cross with male elders) to produce F1 plants that will change the morphological and agronomic character. This research was conducted at the screen house area in the Faculty of Agriculture, Mulawarman University, Until the of January 2018 to September 2018. The results of this identification showed that from 161 spikelet castrated obtained as many as 60 grains with a percentage of fertility 37.27%, and then sowing as many as 30 seeds (50%), plants that successfully grew and could be used there were 21 plants (70%) character morphology and agronomic on F1 plants more dominant in the character of Pandan Ungu rice. The dominan characters are leaf color, ligula color, uricle color, midrib color, leaf surface, stigma color, grain end color, lemma and palea color, number of wildings, breed ability, number of productive wildingss, panicle type, yellowing of leaves, diameter of root stock, and harvesting the crop.